2012
DOI: 10.2108/zsj.29.327
|View full text |Cite
|
Sign up to set email alerts
|

Piscidin-1, an Antimicrobial Peptide from Fish (Hybrid Striped BassMorone saxatilisxM. chrysops), Induces Apoptotic and Necrotic Activity in HT1080 Cells

Abstract: Piscidin-1, a 22-residue cationic peptide isolated from mast cells of a hybrid striped bass, has potent antimicrobial activities against both gram-positive and -negative bacteria. To date, there is no report of its antitumor activity on any tumor cell lines. In this study, we examined the antitumor activity of a synthetic piscidin-1 peptide against several human cancer cell lines using an MTS assay and soft-agar colony-formation assay. We found that a low dose of piscidin induces both apoptosis and necrosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 18 publications
2
57
0
Order By: Relevance
“…Previously it has been reported that piscidin-1, a cationic peptide isolated from the mast cells of hybrid striped bass (23), also causes apoptosis and necrosis at a low concentration and necrotic effect at a high concentration for a short period in HT1080 cells (24). Piscidin-1 has a net charge of +3 and HaA4 has a net charge of +2 at pH 7.0, which might function in the anticancer activity.…”
Section: Haa4 Induces Apoptosis and Necrosis In Leukemia Cellsmentioning
confidence: 99%
“…Previously it has been reported that piscidin-1, a cationic peptide isolated from the mast cells of hybrid striped bass (23), also causes apoptosis and necrosis at a low concentration and necrotic effect at a high concentration for a short period in HT1080 cells (24). Piscidin-1 has a net charge of +3 and HaA4 has a net charge of +2 at pH 7.0, which might function in the anticancer activity.…”
Section: Haa4 Induces Apoptosis and Necrosis In Leukemia Cellsmentioning
confidence: 99%
“…The peptide exhibits antimicrobial activity against methicillin-resistant Staphylococcus aureus (24), viruses such as HIV-1 (25), fungi (26), and cancer cells (27). Like other AMPs, piscidin induces dye leakage in model membranes and membrane disruption is proposed to be its primary mechanism of action against bacteria (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…The surfacebound structures of p1 were determined independently by ssNMR and all-atom molecular dynamics (MD) in two different bacterial cell mimics (30). Both methods yielded highly helical structures parallel to the membrane surface, and a [20][21][22][23][24][25][26][27][28][29][30] kink about the helical axis. Subsequent MD simulations demonstrated membrane thinning and induction of positive spontaneous curvature by p1 in 3:1 POPC/POPG bilayers (31).…”
Section: Introductionmentioning
confidence: 99%
“…Piscidin-1 shows significant activity against bacteria, fungi, parasites, and cancer cells (1)(2)(3)(4)(5)(6)(7). It can also neutralize lipopolysaccharide (LPS)-induced proinflammatory responses in macrophage cells (5).…”
mentioning
confidence: 99%